Effects of Bap (6- Benzylaminopurine) in Shoot Regeneration of Pineapple (Ananas Comosus (L) Merr) Cultured in-Vitro (Journal of Science and Technology, 2016)
Growth and development in plants are regulated by the interactions between promotive and inhibitory hormones [1]. Synthetic chemicals with similar physiological activities to these endogenous substances with an ability to modify plant growth are termed plant growth are termed plant growth regulators [2]. Tissue culture (micropropagation), which is a modern tool in Agriculture for rapid clonal (vegetative) propagation, employs some of these synthetic chemicals to bring about desirable changes in plants. The paper reports of the effects of growth regulators BAP (6 – BENZYL AMINOPURINE), a cytokinin, on shoot regeneration. The regulator was investigated for its effect on pineapple plantlet cultured in-vitro on morphogenesis and subsequent ex-vitro. The concentration of BAP in the culture medium significantly affected morphogenesis. A mean total of 108.5 shoots were regenerated within four weeks from 20 original shoots cultured on medium containing 1 mg/l BAP.